Stimulating consumption — an alternative? - G. Müller-Heumann; R. Böhringer (Intereconomics, 1973)
In view of the preponderant role investments play at present in any development policy, it may well be worthwhile examining whether it would not be advisable in drawing up future aid schemes to lay greater emphasis on the stimulation of consumption.
Keywords: 330; Development Strategy